Fused bicyclic piperidines and dihydropyridines by dearomatising cyclisation of the enolates of nicotinyl-substituted esters and ketones - Brice, Heloise; Clayden, Jonathan; Hamilton, Stuart D. (Beilstein Journal of Organic Chemistry, 2010)
The silyl enol ether derivatives of ketones or esters tethered by a hydrocarbon or ether linkage to the 3-position of a pyridine ring undergo dearomatising nucleophilic attack on the ring once it is activated (as an acylpyridinium species) by the addition of methyl chloroformate. The bicyclic dihydropyridine products are in some cases unstable, but may be isolated after hydrogenation as fused bicyclic piperidines.
Keywords: bicyclic; cyclisation; dearomatisation; enol ether; heterocycle; pyridine; quinoline

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Vo, N. T.; Pace, R. D. M.; O’Hara, F.; Gaunt, M. J. (J. Am. Chem. Soc., 2008)
and references therein

(untitled) - Hamamoto, H.; Anilkumar, G.; Hirofumi, T.; Kita, Y. (Chem.–Eur. J., 2002)

(untitled) - Dai, M.; Danishefsky, S. J. (Heterocycles, 2009)

(untitled) - López-Ortiz, F.; Iglesias, M. J.; Fernández, I.; Andujar Sanchez, C. M.; Ruiz-Gómez, G. (Chem. Rev., 2007)
(see for review)

(untitled) - Wang, Z.; Xi, Z. (Synlett, 2006)

(untitled) - Nevárez, Z.; Woerpel, K. A. (J. Org. Chem., 2008)

(untitled) - Liu, L.; Wang, Z.; Zhao, F.; Xi, Z. (J. Org. Chem., 2007)

(untitled) - Ruiz-Gómez, G.; Iglesias, M. J.; Serrano-Ruiz, M.; García-Granda, S.; Francesch, A.; López-Ortiz, F.; Cuevas, C. (J. Org. Chem., 2007)

(untitled) - Ruiz-Gómez, G.; Francesch, A.; Iglesias, M. J.; López-Ortiz, F.; Cuevas, C.; Serrano-Ruiz, M. (Org. Lett., 2008)

(untitled) - Kumaran, R. S.; Brüdgam, I.; Reissig, H.-U. (Synlett, 2008)

(untitled) - Ovens, C.; Martin, N. G.; Procter, D. J. (Org. Lett., 2008)

(untitled) - Clayden, J.; Kenworthy, M. N.; Helliwell, M. (Org. Lett., 2003)

(untitled) - Clayden, J.; Kenworthy, M. N. (Org. Lett., 2002)

(untitled) - Clayden, J.; Menet, C. J.; Mansfield, D. J. (Org. Lett., 2000)

(untitled) - Clayden, J.; Tchabanenko, K.; Yasin, S. A.; Turnbull, M. D. (Synlett, 2001)

(untitled) - Ahmed, A.; Clayden, J.; Yasin, S. A. (Chem. Commun., 1999)

(untitled) - Ahmed, A.; Clayden, J.; Rowley, M. (Chem. Commun., 1998)

(untitled) - Ahmed, A.; Clayden, J.; Rowley, M. (Synlett, 1999)

(untitled) - Bragg, R. A.; Clayden, J. (Tetrahedron Lett., 1999)

(untitled) - Clayden, J.; Purewal, S.; Helliwell, M.; Mantell, S. J. (Angew. Chem., Int. Ed., 2002)

Strategies and Tactics in Organic Synthesis - Clayden, J. (Total synthesis of kainoids by dearomatizing anionic cyclisation, 2004)

(untitled) - Clayden, J.; Knowles, F. E.; Baldwin, I. R. (J. Am. Chem. Soc., 2005)

(untitled) - Clayden, J.; Knowles, F. E.; Menet, C. J. (Tetrahedron Lett., 2003)

(untitled) - Clayden, J.; Knowles, F. E.; Menet, C. J. (Synlett, 2003)

(untitled) - Clayden, J.; Menet, C. J.; Tchabanenko, K. (Tetrahedron, 2002)

(untitled) - Clayden, J.; Tchabanenko, K. (Chem. Commun., 2000)

(untitled) - Ahmed, A.; Bragg, R. A.; Clayden, J.; Tchabanenko, K. (Tetrahedron Lett., 2001)

(untitled) - Bragg, R. A.; Clayden, J.; Bladon, M.; Ichihara, O. (Tetrahedron Lett., 2001)

(untitled) - Clayden, J.; Menet, C. J.; Mansfield, D. J. (Chem. Commun., 2002)

(untitled) - Clayden, J.; Kenworthy, M. N. (Synthesis, 2004)

(untitled) - Clayden, J.; Read, B.; Hebditch, K. R. (Tetrahedron, 2005)

(untitled) - Clayden, J.; Hamilton, S. D.; Mohammed, R. T. (Org. Lett., 2005)

(untitled) - Clayden, J.; Hennecke, U. (Org. Lett., 2008)

(untitled) - Clayden, J.; Turnbull, R.; Pinto, I. (Org. Lett., 2004)

(untitled) - Clayden, J.; Turnbull, R.; Helliwell, M.; Pinto, I. (Chem. Commun., 2004)

(untitled) - Clayden, J.; Farnaby, W.; Grainger, D. M.; Hennecke, U.; Mancinelli, M.; Tetlow, D. J.; Hillier, I. H.; Vincent, M. A. (J. Am. Chem. Soc., 2009)

(untitled) - Clayden, J.; Dufour, J.; Grainger, D.; Helliwell, M. (J. Am. Chem. Soc., 2007)

(untitled) - Arnott, G.; Clayden, J.; Hamilton, S. D. (Org. Lett., 2006)

(untitled) - Arnott, G.; Brice, H.; Clayden, J.; Blaney, E. (Org. Lett., 2008)

(untitled) - Brice, H.; Clayden, J. (Chem. Commun., 2009)

(untitled) - Raussou, S.; Gosmini, R.; Mangeney, P.; Alexakis, A.; Commerçon, M. (Tetrahedron Lett., 1994)

(untitled) - Yamada, S.; Morita, C. (J. Am. Chem. Soc., 2002)

(untitled) - Rudler, H.; Denise, B.; Xu, Y.; Parlier, A.; Vaissermann, J. (Eur. J. Org. Chem., 2005)

(untitled) - Bosch, J.; Bennasar, M.-L. (Synlett, 1995)

(untitled) - Rudler, H.; Parlier, A.; Sandoval-Chavez, C.; Herson, P.; Daran, J.-C. (Angew. Chem., Int. Ed., 2008)

(untitled) - Onaka, M.; Ohno, R.; Izumi, Y. (Tetrahedron Lett., 1989)

(untitled) - Tanouchi, T.; Kawamura, M.; Ohyama, I.; Kajiwara, I.; Iguchi, Y.; Okada, T.; Miyamoto, T.; Taniguchi, K.; Hayashi, M. (J. Med. Chem., 1981)